If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3p+2+3p=-2(p+8)-4(6-2p)
We simplify the equation to the form, which is simple to understand
3p+2+3p=-2(p+8)-4(6-2p)
Reorder the terms in parentheses
3p+2+3p=+(-2p-16)-4*(6-2p)
Remove unnecessary parentheses
+3p+2+3p=-2p-16-4+*(+6-2p+)
Reorder the terms in parentheses
3p+2+3p=-2p-16+(-24+8p)
Remove unnecessary parentheses
+3p+2+3p=-2p-16-24+8p
We move all terms containing p to the left and all other terms to the right.
+3p+3p+2p-8p=-16-24-2
We simplify left and right side of the equation.
p=-42
0=-42
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 12y+6=6(2y-1) | | (3*18)+20=x | | 2a-9=20+5 | | -10.74+1.7g=2.3g | | (5x-16)+(2x-4)= | | -2+4n=8n+6 | | -16k+10=-14k | | 4x+(x+4)+10(x-1)=288 | | -16k+10=-14 | | x-11=1+3x | | 7+3x-9=2x+6-x | | 3(c-6)+2c=5c | | 7n+54=180 | | 17s-2=16s-19 | | -7(1-5v)=54 | | 3(a-6)+4=-20+5a | | 6+5x-6=4x+8-x | | -10u+14=-20-11u+3u | | 7(2)-5(3)+4= | | -15+5n=n+5 | | (x^3+x^2+x+1)(18x-18)= | | 10-4x=3x-9x+40 | | x+6=4x^2 | | 12x-4=43 | | 180=4n+34 | | -10r+7=-2r+2-9r | | 1420=-680+420d | | yx=0.8 | | 180=5n+125 | | 10-m=9m-10 | | (x^3)-8(x^2)+11x+2=0 | | 13=-d+20 |